The biology of Colletotrichum acutatum - Phillip S. Wharton; Javier Diéguez-Uribeondo (Anales del Jardín Botánico de Madrid)
Colletotrichum acutatum is major pathogen of fruit crops, causing economically important losses of temperate, subtropical and tropical fruits worldwide. However, few studies have been carried out on key aspects of its biology. This is mainly because traditionally isolates of C. acutatum were often wrongly identified as C. gloeosporioides. Effective separation of the two species was not possible until the introduction of molecular tools for taxonomy. The life cycle of C. acutatum comprises a sexual and an asexual stage and much remains to be resolved regarding the genetics of sexuality and the effects of the sexual stage on population structure. Colletotrichum acutatum exhibits both infection strategies described for Colletotrichum species, i.e. intracellular hemibiotrophy and subcuticular-intramural necrotrophy, and may also undergo a period of quiescence in order to overcome resistance mechanisms in immature fruit such as pre-formed toxic compounds and phytoalexins, or due to the unsuitability of unripe fruit to fulfill the nutritional and energy requirements of the pathogen. Colletotrichum acutatum may overwinter as mycelium and/or appressoria in or on different parts of the host. Conidia are water-born and spread by rain episodes so infections are usually highest during the wettest periods of the growing season. Current management strategies for this fungus comprise the exploitation of cultivar resistance, cultural, chemical, and biological control methods, and preventive strategies such as disease-forecasting models. This review focuses on the current knowledge of biological aspects of C. acutatum and related Colletotrichum species and includes a discussion of the progress towards their control.